The Effect of Capacitors on Frequency Response Amplifier IC TDA2030 as Band-Pass Filter - Ferdyanto Ferdyanto; Ade Fikri Fauzi; Mufti Ahmad Fadilah; James Julian; Armansyah Armansyah (ELKHA : Jurnal Teknik Elektro, 2022)
Amplifier is used as an input waveform amplifier by increasing the voltage using an IC power supply. TDA2030 is an amplifier IC with an Output Transformer Less (OTL) type. The amplifier can operate with a voltage of 12 Volt, 1.5 Ampere. The circuit design process uses Proteus software with a universal reference to the TDA2030 datasheet. Proteus experimental results can be seen by simulating the frequency response. Frequency response tests were carried out to obtain filter used for assemble the circuit to produce an ideal Band-pass filter. Then using Digital Oscilloscope, we can observe difference between waves getting emphasis and those they are not. The objective of this study is to determine the value of capacitor C3 with a good  (frequency cut low). Changing value of C3 can produce the desired BPF output. In the experiment, capacitor C3 0.1uf obtained emphasizes low frequencies between 0-250 Hz. Values of C3 with good BPF 47uf and 100uf because the output produced good bass frequency and is suitable for use because the emphasis occurs between 0-5 Hz. On the amplifier IC TDA2030 has made, capacitor C3 with values 47uf and 100uf ideal to be used as BPF because the filter works in a balanced way.